2018
DOI: 10.1590/s1677-5538.ibju.2017.0253
|View full text |Cite
|
Sign up to set email alerts
|

Overactive bladder syndrome and bladder wall thickness in patients with obstructive sleep apnea syndrome

Abstract: ObjectiveThe main objective of the present study was to evaluate the presence of overactive bladder (OAB) syndrome, nocturia, urgency, and urge incontinence in patients with obstructive sleep apnea syndrome (OSAS), and measure bladder wall thickness (BWT) in these patients.Materials and MethodsThe patient group was composed of 38 patients with OSAS. The control group was composed of 15 healthy individuals. All patients were evaluated using the Epworth Sleepiness Scale (ESS) and Overactive Bladder Symptom Score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
3
7
0
2
Order By: Relevance
“…Contrairement à la nycturie que les patients expérimentent exclusivement durant la nuit, l'HAV se manifeste aussi pendant la journée (23). Des altérations multifactorielles, hypoxémiques, psychiques, nerveuses, hormonales et/ou vasculaires ont été suggérées entrainant la destruction nerveuse, la dénervation du detrusor et l'altération du métabolisme de la sérotonine (24).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Contrairement à la nycturie que les patients expérimentent exclusivement durant la nuit, l'HAV se manifeste aussi pendant la journée (23). Des altérations multifactorielles, hypoxémiques, psychiques, nerveuses, hormonales et/ou vasculaires ont été suggérées entrainant la destruction nerveuse, la dénervation du detrusor et l'altération du métabolisme de la sérotonine (24).…”
Section: Introductionunclassified
“…L'incontinence urinaire était détectée chez 39,6% des femmes ayant une HAV. Ils ont observé que le traitement du SAOS par CPAP pendant 3 mois chez 111 femmes souffrant d'HAV, a permis une amélioration statistiquement significative des scores de l'hyperactivité vésicale (OABSS) et l'incontinence urinaire (ICIQ-SF) chez les patientes ayant un SAOS modéré à sévère (p<0,01)(23,24,32). Cependant des études supplémentaires comparatives sont nécessaire pour définir les meilleures stratégies thérapeutiques de l'HAV associée au SAOS(23).Données urodynamiquesQuelques études urodynamiques ont évalué l'évolution des données urodynamiques après traitement par CPAP, chez les patients souffrant de SAOS.…”
unclassified
“…Obesity increased intra-abdominal pressure and led to nocturia 15 . In addition, those with obesity had a higher chance of obstructive sleep apnea, which resulted in nocturnal polyuria and detrusor instability 16 , 17 . One supportive evidence in this study was that the participants with nocturia had a higher IPSS (except times of nocturnal voiding) score, especially with regards to the storage scores.…”
Section: Discussionmentioning
confidence: 99%
“…Severity of OSA was proportional to OAB and urinary incontinence occurrence [50]. A diluted nocturnal urine was predictive of OSA diagnosis, with 88% of sensitivity in patients with daytime OAB symptoms [51], which were more severe in the OSA group than in the control group [52]. Proposed mechanisms for the aforementioned relationship include the intermittent hypoxia induced by OSA; this oxidative stress changes the bladder structurally and functionally [53].…”
Section: Benign Prostate Hyperplasia: Relationship To Nocturia Sleepmentioning
confidence: 99%
“…Proposed mechanisms for the aforementioned relationship include the intermittent hypoxia induced by OSA; this oxidative stress changes the bladder structurally and functionally [53]. Indeed, bladder-wall thickness and OAB symptoms were closely related in OSA patients [52]. However, one study found no increased prevalence of OAB, nocturia, or urgent urinary incontinence symptoms in young male patients with OSA [54].…”
Section: Benign Prostate Hyperplasia: Relationship To Nocturia Sleepmentioning
confidence: 99%